A simple highly sensitive and selective turn-on fluorescent chemosensor for the recognition of Pb2+. Issue 3 (18th January 2017) - Sun, Tao; Niu, Qingfen; Guo, Zongrang; Li, Tianduo
Graphical abstract: Highlights: A simple fluorescent turn-on chemosensorL for Pb 2+ was developed. SensorL exhibited an excellent selectivity and high sensitivity toward Pb 2+ . The quite low detection limit for Pb 2+ was found to be 3.80 × 10 −7  M. The Pb 2+ recognition can function well within a wide pH range. Abstract: A simple highly sensitive and selective turn-on fluorescent chemosensorL based on bis-Schiff-base for Pb 2+ ions was synthesized and characterized by spectroscopic techniques.L having high binding affinity towards Pb 2+ ions of 2.10 × 10 4  M −1 selectively detects Pb 2+ ions with almost no interference among various competitive ions by a 11-fold fluorescent enhancement in CH3 CN/H2 O (95:5, v/v) solution over a wide pH range. Moreover, sensorL displayed a lower detection limit of 3.80 × 10 −7  M, which is low enough for sensing sub-millimolar concentration of Pb 2+ encountered practically.